Prospects of building an agenda for technology transfer policy advocacy in Brazil from international experience - DE OLIVEIRA, LUIZ GUILHERME (Advances in Social Sciences Research Journal, 2018)
The process of developing technological skills, especially for late developing countries such as Brazil, is characterized by high cost and long maturation. The objective of this paper is to support the formulation of local policies related to the transfer of technology through compensation mechanisms, mainly technological, offset type. Although the offset mechanisms are not new in the field of technological public policies between countries, they have different forms of structuring that modify between countries and between sectors of the economy. The present study aims to focus on the offset policies in the defense sector, from selected countries (Sweden, Spain, United Kingdom, Italy, India and Canada) seeking to observe issues such as investment maturation period, focus, legal framework between others. From this it is sought to consider the best practices among selected countries.